PWE-162 Seasonal and diurnal variation in the presentation and severity of acute upper gastrointestinal bleeding. (28th May 2012) - Disney, B R; Watson, R; Blann, A; Lip, G; Tselepis, C; Anderson, M
Abstract : Introduction: Acute upper gastrointestinal bleeding is a medical emergency associated with a significant health burden and risk of mortality. Previous studies have looked for diurnal and seasonal variations in presentation. No studies have addressed these issues in the UK population. Methods: All patients admitted with acute upper gastrointestinal bleeding to Sandwell and West Birmingham Hospitals NHS Trust from 1 January 2009 to 31 December 2009 were included in the study. Diurnal and seasonal differences in presentation were analysed using the χ 2 test; differences in Rockall and Blatchford scores were analysed using the Kruskal–Wallis test followed by the Mann–Whitney U test, with Bonferroni correction, to assess differences between individual groups. Results: Overall, 470 patients with acute upper gastrointestinal bleeding were admitted during the study period. Of these 67.2% were male and 32.8% female. The mean age of patients was 64.0±18.8 years. Significant differences were seen in both diurnal and seasonal variation. Patients were more likely to present between the hours of 12:01–18:00 (p<0.001). Admission rates were lower during the winter months (p=0.028). The Rockall score showed significant diurnal variation (p=0.048). No diurnal variation was seen in the Blatchford score (p=0.39). Conclusion: Acute upper gastrointestinal bleeding shows a significant diurnal and seasonal variation in presentation. Diurnal variation is observed in Rockall scores, although this is of doubtful clinical relevance. The variation in presentation of acute upper gastrointestinal bleeding may have implications for the provision of endoscopy services. Competing interests: None declared.